Attitudes and perceptions of health schools’ students toward mobile learning: a cross-sectional study - Faten Hamad; Suha AlMuhaissen; Christine Urquhart; Ruba Tarawneh; Muzdalifa Asaad; Mays Abu-Ajamieh (BMC Medical Education)
Abstract Background Mobile devices are now widely and extensively used by university students. With the rapid advancement in technology, mobile learning has become an important educational model, particularly for health schools’ students. This research aims to investigate the attitudes of health schools’ students in Jordan towards mobile learning, as well as their perceptions of mobile learning advantages and disadvantages compared to the traditional face-to-face learning model. Methods A quantitative research design was employed, with data collected through a web-based cross-sectional descriptive questionnaire using Google® Forms. The questionnaire was distributed to 703 students across the five health schools at the University of Jordan, with 690 students completing it, resulting in a response rate of 98.2%. Results Among the participants, 92.6% reported using smartphones as their primary device for mobile learning, and 98.8% relied on YouTube as their main educational website. Over two-thirds of the surveyed students expressed concerns about feeling isolated during mobile learning. A majority (64.9%) believed that there is a need for developing learning applications with offline accessibility, while 62.3% emphasized the importance of adapting exam platforms to be compatible with all mobile devices. Approximately 63% of the participants felt that mobile learning should complement face-to-face learning. Significant differences (p < 0.05) were found among the different health schools’ students regarding the purposes for which they used mobile learning, such as watching educational videos or accessing the university library website. Significant differences (p < 0.05) were also observed between groups concerning the perceived advantages of mobile learning. Conclusion Students from the health schools at the University of Jordan confirmed that they use mobile devices, primarily smartphones, to support their learning. However, the use of these devices for educational purposes was not highly advanced, with a preference for face-to-face learning methods. The findings of this research will assist policymakers and educators in planning infrastructure and curricula for health education in Jordan, utilizing mobile learning to better meet the needs of an increasing student population.